The Physical Basis of Bacterial Quorum Communication - Hagen, Stephen J (Springer, 2015)
Many bacterial species engage in the behavior known as quorum sensing (QS), which can be described as the regulation of gene expression in response to changes in the bacterial population density [1]. The bacteria synthesize and release diffusible small molecules known as autoinducers, which accumulate in the environment. When the concentration of autoinducer (AI) reaches a threshold level, indicating the presence of a “quorum” of cells, the population responds as a whole by activating certain gene regulatory networks, leading to colony-wide changes in phenotype. A wide range of bacterial behaviors are now known to be regulated through QS. These include biofilm production, genetic competence, bioluminescence, vari ous types of motility, and the production of exoenzymes, toxins, bacteriocins, and other types of virulence factors and secreted products. As the collective production and detection of the autoinducer signal allows the entire population to synchronize gene regulation, quorum sensing (QS) is a form of chemical communication and a social behavior. Accordingly it has attracted tremendous interest from researchers in many fields...